Довготривала релаксація фотопровідності у твердих розчинах Cu1-xZnxInS2 - Кажукаускас, Вайдотас; Новосад, Олексій; Вайнорюс, Неймантас; Божко, Володимир; Сакавічюс, Андрюс; Козер, Василь; Яноніс, Вітаутас; Божко, Неоніла; Kazukauskas, Vaidotas; Novosad, Oleksiy; Vainorius, Neimantas; Bozhko, Volodymyr; et al. (Східноєвропейський національний університет імені Лесі Українки, 2013)
На основі уявлень про рівні прилипання проаналізовано результати досліджень релаксації фотопро- відності твердих розчинів n-Cu1-xZnxInS2 в інтервалі температур 30–100 К. Показано, що в Cu1-xZnxInS2 має місце довготривала релаксація фотопровідності (101–103 с), яка контролюється s та r-центрами рекомбінації. Визначена глибина залягання рівнів прилипання становила ~0,1–0,2 еВ.; Photoconductivity kinetics in CuInS2–ZnIn2S4 solid solutions has been studied. An effect of long-term relaxation processes (~101–103 s) at T≈27–100 К was revealed. Data on photoconductivity relaxation are analyzed in terms of attachment levels. Here the nonequilibrium conductivity relaxation kinetic of CuInS2–ZnIn2S4 solid solution corresponds to the case of the exponential recombination. The main parameters characterizing the photoconductivity kinetic were determined. It is shown that as the temperature increases, the relaxation time of the slow component and fast component decreases. The contribution of the slow component also decreases whereas fast component increases. It is shown that relaxation of photoconductivity is controlled by multicenter recombination in which both «fast» and «slow» recombination centers participate.
Long-term Relaxation of Photoconductivity in Cu1-xZnxInS2 solid solutions
Keywords: тверді розчини; фотопровідність; релаксація; центри рекомбінації; solid solutions; photoconductivity; relaxation; recombination centers